PROSES PELAKSANAAN TERAPI RASIONAL EMOTIF - H.M.Sattu Alang (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Emotive Rational Therapy is a form of therapy that seeks to improve rational thinking patterns and eliminate irrational thinking patterns. This therapy is an attempt to re-educate by giving the task to be done by the patient and teach certain strategies to strengthen the thought process. People have the ability to confront their own value systems and indoctrinate themselves with different beliefs, ideas, and values. As a result, they will behave differently from the way they behaved in the past. Because they can think and act to make themselves change, they are not victims of passive past conditioning. The purpose of emitive rational therapy is to help individuals cope with their behavioral and emotional problems to bring them a happier, healthier and more fulfilled life. In simple and general purpose of this therapy is to help clients to free themselves from ideas that are not logical and to learn ideas that are logical and realistic as a replacement. The Rational Emotive Therapy Steps are as follows: (a) The therapist tries to show that the client's way of thinking must be logical then helps how and why the client arrived in such a way, showing the pattern of the relationship between logical thoughts and unhappy feelings or with emotional disturbances in its natural. (b) Show the client that he is able to maintain his behavior then it will be disturbed and this illogical way of thinking is what causes disturbances as felt. (c) Aiming to change the client's way of thinking by discarding illogical ways of thinking (d) In this counselor assigns clients to try to take certain actions in real situations. The techniques used are emotive, cognitive and behavioral techniques.